Direct Synthesis of Chain‐end‐functionalized Poly(3‐hexylthiophene) without Protecting Groups Using a Zincate Complex. Issue 11 (8th June 2020) - Inagaki, Shin; Yamamoto, Takuya; Higashihara, Tomoya
Abstract : Back Cover : In article 2000148, Tomoya Higashihara and co‐workers synthesize chain‐end‐functionalized poly(3‐hexylthiophene)s (P3HTs) with benzyl alcohol, phenol, and benzoic acid groups via Negishi catalyst‐transfer polycondensation using a zincate complex. The chain‐end‐functionalized P3HTs have controlled number‐average molecular weights and high chain‐end functionality.